2022
DOI: 10.3171/2021.10.focus21526
|View full text |Cite
|
Sign up to set email alerts
|

Does robot-assisted navigation influence pedicle screw selection and accuracy in minimally invasive spine surgery?

Abstract: OBJECTIVE The accuracy of percutaneous pedicle screw placement has increased with the advent of robotic and surgical navigation technologies. However, the effect of robotic intraoperative screw size and trajectory templating remains unclear. The purpose of this study was to compare pedicle screw sizes and accuracy of placement using robotic navigation (RN) versus skin-based intraoperative navigation (ION) alone in minimally invasive lumbar fusion procedures. METHODS A retrospective cohort study was conducted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 42 publications
2
37
0
Order By: Relevance
“…Meanwhile, another study by Devito et al did not publish the levels that were instrumented limiting the conclusions which can be drawn [11]. This study demonstrates that robot-assisted pedicle screws in the thoracolumbar spine during acute, traumatic surgery are both feasible and accurate which is in agreement with previous studies demonstrating the accuracy of robot-assisted pedicle screws [20][21][22]. However, a large, randomized trial should be performed to confirm or disprove the superiority of robot-assisted pedicle screw placement as compared to pedicle screws placed with other techniques in the thoracic spine during an acute, traumatic setting.…”
Section: Discussionsupporting
confidence: 87%
“…Meanwhile, another study by Devito et al did not publish the levels that were instrumented limiting the conclusions which can be drawn [11]. This study demonstrates that robot-assisted pedicle screws in the thoracolumbar spine during acute, traumatic surgery are both feasible and accurate which is in agreement with previous studies demonstrating the accuracy of robot-assisted pedicle screws [20][21][22]. However, a large, randomized trial should be performed to confirm or disprove the superiority of robot-assisted pedicle screw placement as compared to pedicle screws placed with other techniques in the thoracic spine during an acute, traumatic setting.…”
Section: Discussionsupporting
confidence: 87%
“…Table 5 provides an overview of the accuracies of 3D navigation for MISS as reported in literature and the 98.1% accuracy obtained with the ON in this study, is in line with these published reports. The accuracy results of ON were also comparable to the pedicle screw placement accuracies of robotic systems [15][16][17].…”
Section: Discussionsupporting
confidence: 58%
“…Molliqaj et al [ 12 ] reported a clinically acceptable screw placement accuracy under robotic guidance of up to 93.4%. Karim et al [ 15 ]found that surgeons, with the assistance of a robot, tended to choose larger-diameter and longer screws in the minimally invasive surgery-transforaminal lumbar interbody fusion when compared with intraoperative navigation alone, particularly when using sizes that they may have previously thought to be too large. Our results are somewhat similar to these studies.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, there have been many studies on the robot's advantage in accuracy and selection of pedicle screws, offering benefits for both patients and surgeons [15,[19][20][21]. Preoperative CT is used to plan screw trajectories, and intraoperative fluoroscopy is applied to register images.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation